Programma: 11 september tot 8 oktober: Bols Taverne: Expositie Ronald Hammega, Kees Evers, Aloys Ginjaar (1976)
Programma: 11 september tot 8 oktober: Bols Taverne: Expositie Ronald Hammega, Kees Evers, Aloys Ginjaar.